“SELF-FULFILLMENT” SEBAGAI ENTREPRENEURISM PELAKU USAHA MIKRO (STUDI ETNOGRAFI PADA PEMILIK WARUNG KOPI EMPAT SAUDARA) - Muhamad Radhiya Rizky Raviandy Rushandy; Nur Fikri Fadhilah; Mohamad Yanuar Burhanudin; Budiawati Supangkat; Margo Purnomo; Hardian Eko Nurseto (Universitas Andalas, 2022)
Research around the emergence of entrepreneurship usually pays special attention to aspects of motivation and driving factors that support a decision to become an entrepreneur. Self-fulfillment is one of the driving factor that is still abstract in its meaning. This article aims to provide a deeper meaning of self-fulfillment, viewed from a cultural perspective as a result and shaper of the thought process, by looking at the meaning of entrepreneurism value for an entrepreneur who runs a micro business in a coffee shop. The method used is case study with ethnography approach which utilizes participation observation on Warung Kopi Empat Saudara in Kliningan, Bandung. The study's results found that the meaning of self-fulfillment can be found and described in cultural aspects such as the fulfillment of religious and social values. The fulfillment of religious values can be found in religious freedom to pray during work, described as giving workers access to pray, honesty in business, and having muslims as workers. While the fulfillment of social values is described as helping each other, upholding responsibility to the community, and keeping life harmonious.